2020
DOI: 10.3390/coatings10121226
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Reinforcement and Deacidification of Paper Documents: Application of Lewis Base—Chitosan Nanoparticle Coatings and Analytical Characterization

Abstract: To delay acidification and deterioration during natural aging, deacidification and reinforcement of paper manuscripts have been the most important technologies to prolong the life of objects. Herein, a novel approach for the conservation of paper manuscripts is proposed using chitosan nanoparticles as Lewis base that leads to both deacidification and strengthening of paper in one-step. Chitosan nanoparticles were prepared through physical ball grinding method and characterized via scanning electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…While this is happening, excessive sun exposure would accelerate UVA and UVB radiation’s breakdown of cellulose molecules. Therefore, in order to delay the degradation in the maintenance of these paper collections, preventive conservation is required [ 41 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Application Of Polyelectrolyte Coatings For the Protection O...mentioning
confidence: 99%
See 1 more Smart Citation
“…While this is happening, excessive sun exposure would accelerate UVA and UVB radiation’s breakdown of cellulose molecules. Therefore, in order to delay the degradation in the maintenance of these paper collections, preventive conservation is required [ 41 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Application Of Polyelectrolyte Coatings For the Protection O...mentioning
confidence: 99%
“…Jia et al claim that four typical fungi found in libraries and museums are used to test the antibacterial effectiveness of paper covered with CH nanoparticles. The outcomes demonstrate the potent antibacterial activity of CH nanoparticles [ 108 ]. According to Totolin and colleagues, the plasma polymer P(MMA-co-EtA) film formed by low pressure non equilibrium plasma polymerization allows the creation of a “polymer-like” structure while maintaining the functions of the monomers [ 113 ].…”
Section: Application Of Polyelectrolyte Coatings For the Protection O...mentioning
confidence: 99%
“…The treated papers had higher thermal and UV stability and exhibited an inferior loss of strength. For papers coated with chitosan nanoparticles, the protection is due to the formation of chitosan protective layer when the nanoparticles combined with H 2 O and H + , the deacidification of the paper being produced (a pH increase from 5 to 7 being recorded), also increasing tensile strength and folding endurance [173].…”
Section: Coatings For Miscellaneous Applicationsmentioning
confidence: 99%
“…Calcium hydroxide, calcium bicarbonate, magnesium hydroxide, magnesium bicarbonate and magnesium oxide are the most commonly used deacidification reagents [ 8 , 9 , 10 , 11 ]. As paper acidification causes paper relics to undergo embrittlement and decay, to form dregs, and even to break upon a single touch, reinforcement treatment should be an essential step for these acidic paper relics [ 12 , 13 , 14 ]. Especially, for acidic paper relics with lost mechanical strength, a back support to enhance their mechanical strength is usually required.…”
Section: Introductionmentioning
confidence: 99%